Surgery for bilateral vocal fold paralysis: Systematic review and meta-analysis - Titulaer, Kai; Schlattmann, Peter; Guntinas-Lichius, Orlando (Frontiers in Surgery, 2022)
Objectives: To determine the decannulation rate (DR) and revision surgery rate after surgery for bilateral vocal fold paralysis (BVFP). Data Sources: Five databases (MEDLINE, PubMed, Embase, Web of Science, Scopus) were searched for the period 1908 – 2020. Methods: The systematic literature review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were pooled using a random-mixed-effects model. Randomized controlled trials and non-randomized studies (case-control, cohort, and case series) were included to assess DR and revision surgery rate after different surgical techniques for treatment of BVFP. Results: The search yielded 857 publications, of which 102 with 2802 patients were included. DR after different types of surgery was: arytenoid abduction (DR 0.93, 95%-confidence interval [CI]: 0.86-0.97), endolaryngeal arytenoidectomy (DR 0.92, 95%-CI: 0.86-0.96), external arytenoidectomy (DR 0.94; 95%-CI: 0.71-0.99), external arytenoidectomy and lateralisation (DR 0.87; 95%-CI: 0.73-0.94), laterofixation (DR 0.95; 95%-CI: 0.91-0.97), posterior cordectomy (DR 0.97, 95%-CI: 0.94-0.99), posterior cordectomy and arytenoidectomy (DR 0.98, 95%-CI: 0.93-0.99), posterior cordectomy and subtotal arytenoidectomy (DR 0.98, 95%-CI: 0.88-1.00), posterior cordotomy (DR 0.96, 95%-CI: 0.84-0.99), reinnervation (0.69, 95%-CI: 0.12-0.97), subtotal arytenoidectomy (DR 1.00, 95%-CI: 0.00-1.00) and transverse cordotomy (DR 1.0, 95%-CI: 0.00-1.00). No significant difference between subgroups for DR could be found (Q = 15.67, df = 11, p = 0.1540). The between-study heterogeneity was low (τ2 = 2.2627; τ = 1.5042; I2 = 0.0%). Studies were at high risk of bias. Conclusion: BLVP is a rare disease and the study quality is insufficient. The existing studies suggest a publication bias and the literature review revealed that there is a lack of prospective controlled studies. There is a lack of standardized measures that takes into account both speech quality and respiratory function and allows adequate comparison of surgical methods.